Pemberdayaan Masyarakat Sebagai Penggagas Usaha Mikro, Kecil, dan Menengah (UMKM) Bidang Pengolahan Makanan Melalui Pelatihan Pembuatan Tepung Singkong Modifikasi (Mocaf) dari Ketela Pohon - Widyastuti, Catur Rini; Damayanti, Astrilia; Artanti Putri, Dewi; Krisdayanti , Shendy; Noor Ubay, Isnina (J-Dinamika : Jurnal Pengabdian Masyarakat, 2024)
Diversification of processed cassava into mocaf flour has the potential to be developed into products with high economic value. Mocaf flour made through a fermentation process has low HCN content and better organoleptic properties compared to cassava flour. Cassava roots are abundantly available and are the main commodities in Gunungpati, Semarang. On the other hand, the level of community welfare in this area is still low, hence efforts are needed to improve the economy through community empowerment activities. Efforts that can be made are to provide training and assistance in processing the local resources into products that have economic value. The training carried out was processing cassava into mocaf flour with participants from the PKK (Family Welfare Program) group in Ngijo, Gunungpati, Semarang. This training can improve the skills of the participants so that they can initiate the production of mocaf on a micro-enterprise scale. The series of activities that were done during this service program included the research steps and analysis of mocaf characteristics, followed by training in making mocaf flour for the community group and assisting in the initiation of MSMEs that produce mocaf flour.